English Language Training At PP. Raden Rahmad Sunan Ampel Jember - Dwi Nur Hadiyansah; Nuril Firdaus; Musdalifa Musdalifa (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
English training is a crucial component of education, and the need for English proficiency continues to grow in today's increasingly globalized world. As the lingua franca, English has become the language of business, academics, and international communication, making it an essential skill for individuals and businesses alike. English training is not just a subject to be learned, but a life skill that opens up numerous doors and opportunities for personal and professional development. In English training, students enhance their Part of Speech and Tenses knowledge, enabling them to effectively communicate in English. The importance of English training in education has been recognized at Raden Rahmad Sunan Ampel Jember, where this training was conducted from July 24th to 26th to help enhance students' language skills. Forty-seven students (21 male and 26 female) participated in the training. The five tutors leading the training provided the students with material handbooks as well after conducting a pre-and post-test to assess their language skills. The training was a success, with the results showing that the student's English skills were improved after the training. English training is a valuable investment in students' future and highlights the importance of language skills in today's world. As more and more people learn English, the demand for English skills and proficiency will continue to grow, making it an invaluable skill for individuals and businesses alike.